The Infuleence Of The Head Of The Village Office On The Effectiveness Of Employee Perfirmance At Ardipura Village Office,South JayaPura District,Jayapura City - Gobai, Frediel (Intitute of Computer Science (IOCS), 2025)
This study is entitled